Techniques Graphic Design in “Puzzle” Games (Al-Academy, 2024)
Modern design techniques contribute to the achievement of high quality printed designs for games "Puzzle" is clearly marked with bright colors, measurements and sizes consistent between the Typographic elements And the designs are kept on the computer continuously scalable, It develops cognitive, sensory and motor skills that need focus and reasonable thinking. which can be effective in stimulating children's learning, The design idea has been studied in terms of simplicity, complexity, types of traditional and digital basil games, and the use of constructive elements in design such as graphics, forms, Typograph elements and their relationships in the design of game forms The study focuses on an analysis of some of the techniques used in designing "Puzzle" games.